Israel and the Assyrians : Deuteronomy, the succession treaty of Esarhaddon, and the nature of subversion - Crouch, Carly L. (Carly Lorraine), 1982- (Atlanta: : SBL Press, 2014)
"This volume investigates Deuteronomy's subversive intent within its social context, and reconsiders the relationship between Deuteronomy and Assyria, its relationship to ancient Near Eastern and biblical treaty and loyalty oath traditions, and the relevance of its treaty affinities to discussions of its date"--
Includes bibliographical references and index.
Keywords: Esarhaddon, -- King of Assyria, -- -669 B.C.; Bible. -- Criticism, interpretation, etc; Assyro-Babylonian literature -- Relation to the Old Testament; Assyria -- Religion